حضرت ابوبکرہ ثقفیؓ کی روایات ِاخبارِغیب:تحقیقی و تجزیاتی مطالعہ: Hazrat Abū Bakrah Thaqafi’s Traditions Regarding Akhbār-e-Gaib: A Research and Analytical Study (Al-Qamar, 2025)
This research offers a detailed analytical study of the narrations of Hazrat Abu Bakrah Thaqafi (RA) concerning akhbār al-ghayb—the Prophet Muhammad’s ﷺ divinely inspired foreknowledge of unseen realities. These narrations encompass predictions of socio-political upheavals, the rise and fall of empires, trials and tribulations (fitan), and the moral and spiritual decline of the Muslim community. Far from being mere reports of future events, they provided practical guidance for the Ummah, urging steadfastness, neutrality in civil strife, and preservation of essential Islamic sciences such as the Qur’an and ‘ilm al-fara’id. Hazrat Abu Bakrah (RA) emerges as a key transmitter of such traditions, which underscore the truthfulness of Prophethood, the miraculous nature of the Prophet’s ﷺ knowledge, and his role in guiding the community across historical crises. The study highlights the prophetic characteristics (khaṣā’iṣ al-nubuwwah) manifested in these traditions—such as insight into hidden realities, accurate foretelling of historical events, and spiritual remedies for the Ummah—demonstrating that these narrations are not only evidence of divine connection but also a timeless source of intellectual, social, political, and spiritual guidance for Muslims throughout history and in contemporary times.
Keywords: Prophetic Foreknowledge, Rise and Fall of Empires, Islamic Eschatology, Truthfulness of Prophethood, Khasa’is al-Nubuwwah, Fitan (Trials and Tribulations)